Major Gynaecological Operation Performed at Medical University of Bangladesh: Experience of 140 Cases - Khatun, Mahmuda; Banu, Dewan Sahida; Sultana, Rifat; Millat, Md Asadul; Mondal, Dipika Rani; Mahmud, Shahabuddin; Chowdhury, Faiza (Journal of Current and Advance Medical Research, 2018)
Background: Major gynaecological operations are frequently performed for the treatment of different surgical causes. Objectives: The purpose of the present study was to see the surgical outcomes of different major gynaecological operation performed at medical university of Bangladesh. Methodology: This descriptive type of cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at Bangabandhu Sheikh Mujib Medical University, Dhaka from August 2002 to January 2003 for a period of six (6) months. All the women who were undergone major gynaecological operation at any were selected as study population. Minor gynaecological operation cases were excluded from this study. The data were collected by face to face interview. The age, weight, socio-economic condition, nutritional status and anaemia were recorded. Result: A total number of 140 patients were undergone major gynaecological surgeries of which majority were abdominal hysterectomy (57.1%), vaginal hysterectomy (24.3%), salpingo-oophorectomy or ovarian cystectomy (9.3%). The mean age with SD of the study population was 43.91± 9.45 years. Majority were presented with mild anaemia (51.4%). Majority were free of wound infection (92.8%). Conclusion: In conclusion abdominal hysterectomy is the most common major gynaecological operation performed with few wound infection rate. Journal of Current and Advance Medical Research, July 2016;3(2):47-50